2008
DOI: 10.1007/s00414-008-0270-2
|View full text |Cite
|
Sign up to set email alerts
|

A case of hunting death due to an overpenetrated bullet

Abstract: The authors report the case of a death which occurred during wild boar hunting. The scene details revealed that the victim and the beast were aligned in the visual shooting path and the victim had been struck by overpenetrating bullet shot by his friend on the neighbouring stand. The fatal entrance wound was on the victim's left chest. The authors emphasise the importance of the exhaustive forensic investigation, including autopsy of the beast, in cases like this, in order to distinguish accident from homicide. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Vital conclusions in the present case were only achieved by the close cooperation of forensic pathology and the police services; this once more highlights the overriding importance of an interdisciplinary approach in the investigation of firearm deaths [17,20].…”
Section: Discussionmentioning
confidence: 55%
“…Vital conclusions in the present case were only achieved by the close cooperation of forensic pathology and the police services; this once more highlights the overriding importance of an interdisciplinary approach in the investigation of firearm deaths [17,20].…”
Section: Discussionmentioning
confidence: 55%
“…In forensic medicine literature, there exist numerous case descriptions of homicides that remained undetected during the external post-mortem examination but were finally revealed in the course of a subsequent autopsy [1,2,5,8,12,16]. Scientific investigations have shown that in Germany at least half of the homicides remain unrevealed.…”
Section: Discussionmentioning
confidence: 94%
“…Hunting-related deaths may derive from suicide, homicide, and accident, and sometimes it is very hard to distinguish between them [4,5]. According to the Italian Institute of Statistics (ISTAT), in 2012 hunters represented approximately 2% of the entire Italian population.…”
Section: Discussionmentioning
confidence: 99%